Pengaruh Kompensasi dan Gaya Kepemimpinan terhadap Loyalitas Karyawan di Rumah Sakit Bhakti Husada Cikarang – Bekasi - Soedjatmoko; Sarmin; Saraswati, Ririn Uke (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of increasingly sophisticated technology requires corporate organisations to be able to compete for the continuity of the company's operations. Reliable and qualified human resources are needed in carrying out company operations. It will be very difficult for companies to achieve targets and goals and win business competition, if not supported by employees who have high loyalty. Loyalty is an employee's loyal attitude towards the company where he works to maintain or protect the company and make optimal contributions for the achievement of company goals. The purpose of this study was to determine the effect of compensation and leadership style on employee loyalty at Bhakti Husada Hospital Cikarang Bekasi both partially and simultaneously. This study uses associative research with quantitative research methods. The sampling technique uses the slovin formula with a margin of error of 5%. The data collection technique used a questionnaire as many as 100 respondents of Bhakti Husada Cikarang Bekasi Hospital employees. The analysis technique used is multiple linear regression analysis using SPSS version 26 statistical analysis. Based on the results of the study, it can be seen that Compensation has a positive and significant effect on employee loyalty at Bhakti Husada Hospital Cikarang Bekasi by looking at the t test results obtained t count 5.692> t table 1.984 and a significance value of 0.00 < 0.05. Leadership style has a positive and significant effect on employee loyalty at Bhakti Husada Hospital Cikarang Bekasi by looking at the t test results obtained t count 8.206> t table 1.984 and a significance value of 0.00 <0.05. Compensation and leadership style simultaneously have a positive and significant effect on employee loyalty at Bhakti Husada Hospital Cikarang Bekasi by looking at the results of the F test obtained F count 38.613> F table 3.09 and a significance value of 0.00 <0.05